Continued warming of deep waters in the Fram Strait - S. Karam; C. Heuzé; M. Hoppmann; L. de Steur (Ocean Science, 2024)
The Fram Strait is the only deep gateway between the Arctic and the rest of the World Ocean, and it is thus a key region to understand how the deep Arctic will evolve. However, studies and data regarding the deep ocean are scarce, making it difficult to understand its role in the climate system. Here, we analyse oceanographic data obtained close to the Fram Strait sill depth of 2500 m by two long-term mooring locations (F11 and HG-FEVI) in the Fram Strait between 2010–2023 to investigate long-term changes in the hydrographic properties. For additional context, we compile hydrographic profile data from the 1980s for the adjacent basins: the Greenland Sea and the Eurasian Basin. At mooring F11 in the western Fram Strait, we find a clear seasonality, with increased Greenland Sea Deep Water (GSDW) presence during summer and increased Eurasian Basin Deep Water (EBDW) presence during winter. Evaluating long-term changes, we find a modest temperature increase of ∼ 0.1 °C for EBDW from the 1980s. For GSDW, south of the Fram Strait, we find a strong temperature increase of ∼ 0.4–0.5 °C for the same period. The different warming rates have led to GSDW becoming warmer than EBDW since ∼ 2017–2018. This means that the Greenland Sea is no longer a heat sink for the Arctic Ocean at depth but is rather a heat source. It is therefore possible that EBDW temperatures will increase faster in the future.